Search for the X(4140) state in B+→J/[psi][phi]K+ decays - Aaij, Roel; Bachmann, Sebastian; Bien, Alexander; Britsch, Markward; Blouw, Johan; Dordei, Francesca; Eisele, Franz; Färber, Christian; Hansmann-Menzemer, Stephanie; Hartmann, Tobias; Jäger, Andreas; Kreplin, Katharina; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
A search for the X(4140) state in B+→J/ψϕK+ decays is performed with 0.37 fb−1 of pp collisions at √s=7 TeV collected by the LHCb experiment. No evidence for this state is found, in 2.4σ disagreement with a measurement by CDF. An upper limit on its production rate is set, B(B+→X(4140)K+)×B(X(4140)→J/ψϕ)/B(B+→J/ψϕK+)<0.07 at 90% confidence level.